Earthy–Cryptocrystalline vivianite from the trepel deposits near the Suvodol village, Bitola, Macedonia (Geologica Macedonica, 2013)
Within the frame of the trepel deposits (Fig. 1) near Suvodol village, Bitola city it was discovered(Lj. Petreski) an earthy-cryptocrystalline vivianite occurrence. The examined vivianite sample was confirmed byX-ray powder diffraction, chemical, SEM, DTA/TG, infra-red analyses. The treated vivianite sample actually representsa typical earthy-cryptocrystalline variety (Fig. 2) with a peculiar progressive oxidation state of Fe2+ to Fe3+(FeO/Fe2O3 contents nearly 1:1). X-ray powder diffraction, DTA/TG-data are in quite good concordance with literaturedata.